CFD Simulation of Five Blades Archimedes Screw Turbine as Alternative Power Plant for Traditional Fishing Boat - Nikmatullah, Muhammad Iqbal; Muhammad, Andi Haris; Baharuddin; Zulkifli; Rivai, Haryanti (Jurnal Riset & Teknologi Terapan Kemaritiman, 2024)
The need for electrical energy for traditional fishermen has greatly increased, considering that almost all equipment is now powered by electricity. Archimedes screw turbines, which are generally used as micro hydro power plants, especially in rivers or dams that incline, can be used as an alternative power generator for traditional fishing boats. This research aims to determine the performance of a five-blade Archimedes screw turbine using Ansys CFX software. The simulation was carried out with a flow velocity at the inlet boundary of 2.5 m/s using the transient simulation method, in order to obtain information about the flow characteristics around the turbine as the turbine rotates. So that the turbine can rotate during the simulation, the turbine domain is set using a Rigid Body Solution, so that its rotation will be influenced by the flow rate entering the turbine as is done in the laboratory. The results of this research will be used to optimize the performance of the turbine so that it can produce maximum power. From the simulation and analysis carried out, it was obtained that the mechanical power was 0.08 Watts and the hydraulic power was 0.49 Watts with a turbine efficiency of 17.28%. Apart from that, the increase in rotation produced by the turbine due to the hydraulic power of the water is directly proportional to the increase in mechanical power and torque in the turbine. The low value of mechanical power and efficiency obtained in this research is caused by the absence of an inclination angle between the inlet and outlet parts of the turbine.